STUDI PEMANFAATAN TUMBUHAN OBAT BERPOTENSI SEBAGAI ANTI-INFLAMASI DI DESA TELUK BATANG UTARA KECAMATAN TELUK BATANG KABUPATEN KAYONG UTARA - Ardiana, Nisa; Mariani, Yeni; Tavita, Gusti Eva (JURNAL HUTAN LESTARI, 2019)
Medicinal plants are used by the community to treat various diseases, including inflammatory related diseases. The study aim to analysis utilization of medicinal plants have the potential as anti-inflammatory by community in Teluk Batang Utara Village, Teluk Batang Sub-district, Kayong Utara District. Data collection is done by interview and the selection of respondents used the purposive sampling method. The results of research with the community in Teluk Batang Utara Village, Teluk Batang Sub-District, Kayong Utara District, 44 species of medicinal plants, 26 families and 5 habitus that are utilized by the community. The most widely used family is Zingiberaceae (8 species). The highest percentage of habitus is herbs (36.36%).The most widely used plant parts are leaves (43.18%).The most widely used processing method is boiled (35.09%).The most widely used method of use is sticked (44.83%).The most frequently used frequency is three times a days (52.63%).The duration of treatment with the highest percentage is 3-4 days (61.41%). Plants with the highest UV values are Hibiscus rosa-sinesis L (0.54). Inflammatory-related diseases with the highest ICF values are sprains (0.99). Plants with the highest percentage are (100%). The family with the highest FIV value is Zingiberaceae (57.64). Â Keywords: Anti-Inflammation, medicinal plants, Teluk Batang Utara Village.Â